Precision-medicine-toolbox: An open-source python package for the quantitative medical image analysis - Lavrova, Elizaveta; Primakov, Sergey; Salahuddin, Zohaib; Beuque, Manon; Verstappen, Damon; Woodruff, Henry C.; Lambin, Philippe (Software impacts, 2023)
Medical image analysis plays a key role in precision medicine. Data curation and pre-processing are critical steps in quantitative medical image analysis that can have a significant impact on the resulting performance of machine learning models. In this work, we introduce the Precision-medicine-toolbox, allowing clinical and junior researchers to perform data curation, image pre-processing, radiomics extraction, and feature exploration tasks with a customizable Python package. With this open-source tool, we aim to facilitate the crucial data preparation and exploration steps, bridge the gap between the currently existing packages, and improve the reproducibility of quantitative medical imaging research. •Medical imaging demands automation but is lacking methodology standardization.•Medical imaging data curation and exploration are performed in an in-house manner.•Our toolbox is aimed to fill these gaps and enable automated pipelines in radiomics.•The toolbox will increase reproducibility in quantitative medical imaging research.•The community is encouraged to contribute to develop a powerful tool for radiomics.